Penerapan Kurikulum Berbasis Cinta Pada Pelajaran Matematika Kelas 5 di MI Muhammadiyah Romang Lompoa - R, Saenal; Iswatiningsih , Daroe (Journal of Comprehensive Science, 2025)
This study aims to describe the implementation of the Love-Based Curriculum in Mathematics learning for fifth-grade students at Madrasah Ibtidaiyah Muhammadiyah Romang Lompoa. The Love-Based Curriculum emphasizes a learning approach grounded in compassion, empathy, and respect for students as unique individuals. This research employed a qualitative descriptive method with data collected through observation, interviews, and documentation. The results indicate that the implementation of the Love-Based Curriculum in Mathematics learning creates an enjoyable learning atmosphere, fosters students’ intrinsic motivation, and enhances their understanding of mathematical concepts in a more meaningful way. Teachers serve as facilitators and mentors who instill values of love and care in every learning activity, such as through appreciation, empathetic communication, and contextual learning. Challenges encountered include limited time and teachers’ adaptation to the new approach; however, these can be overcome through careful instructional planning. Overall, the application of the Love-Based Curriculum has proven effective in building harmonious relationships between teachers and students and improving the quality of the Mathematics learning process at MI Muhammadiyah Romang Lompoa.